(untitled) (Minerva, 2019)
The Oracles of Hystaspes were often mentioned during Late Antiquity, specially within religious controversies. Nevertheless, no work with such title has been preserved and, therefore, many questions have arisen and caused debate about it. This article analyzes the arguments of the different sides and examines them carefully, based on both Iranian and non-Iranian sources of the preserved Apocalyptic literature. Though it is true that during the imperial period the Oracles of Hystaspes were taken advantage of with political goals or for religious proselytism, a more detailed analysis also reveals that this work has its origin in the syncretism of Iranian apocalyptic literature with Hellenism. We also explain why the new interpretation of Saošiiant based on Kellens’s translation in no way contradicts the traditional interpretation based on Benveniste’s translation.